2021
DOI: 10.2196/27640
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, Acceptability, and Efficacy of Virtual Reality Training for Older Adults and People With Disabilities: Single-Arm Pre-Post Study

Abstract: Background Unlike most virtual reality (VR) training programs that are targeted at homogenous populations, a set of VR games for rehabilitation purposes targeted at a heterogeneous group of users was developed. The VR games covered physical training, cognitive training (classification and reality orientation), community-living skills training, and relaxing scenery experiences. Special considerations for local older adults and people with disabilities were made in terms of hardware choice and softwa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“… 33 , 34 Exergaming-based balance training has previously been shown to provide positive benefits as a potential alternative or complementary therapeutic approach. 35 38 …”
Section: Discussionmentioning
confidence: 99%
“… 33 , 34 Exergaming-based balance training has previously been shown to provide positive benefits as a potential alternative or complementary therapeutic approach. 35 38 …”
Section: Discussionmentioning
confidence: 99%
“…Although VR shows numerous advantages (related to learning motor skills through repetitive practice, performance feedback, and motivation) [46], it also presents some critical issues for patients: insufficient perception of depth and lack of tactile feedback (which, the latter, can cause difficulties when performing virtual tasks that simulate reality) [47,48]. In addition, a recent systematic review results state that patients with advanced age may find VR games complicated or boring and may need supervision to complete the task undertaken [49]. Some of the studies described using VR rehabilitation programs have shown how resistance exercises, stretching, and cognitive rehabilitation can improve the patient's quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…They found that seniors tend to prefer the virtual gamification of existing sports (such as bowling) because it is similar to real games, users are familiar with the gameplay, and have relevant memories with family and friends [30]. Repeatedly moving the limbs and using the muscles can help slow down the deterioration of physical skills [31]. Fixed-cycle training is a non-burdening activity for frail older people, with little impact on their joints [32,33].…”
Section: Elderly Physical Health and Vr Exercise Gamesmentioning
confidence: 99%